Digital Transformation and Collaborative Innovation Public Health Services in Indonesia: A Qualitative - Suprapto Suprapto (Edukasi Ilmiah Indonesia, 2026)
Introduction: Digital transformation has emerged as a strategic approach to improve efficiency, accessibility, and data-driven decision-making in public health services. However, the implementation of digital health initiatives often faces institutional, governance, and coordination challenges. In addition, technological adoption alone may not guarantee sustainable improvements without collaborative innovation among stakeholders. This study aimed to explore how digital transformation and collaborative innovation interact in shaping public health service delivery. Research Methodology: This study employed a qualitative research design using a multiple case study approach. Data were collected through in-depth interviews, focus group discussions, and document analysis involving 18 stakeholders, including policymakers, public health managers, healthcare professionals, information technology personnel, and community representatives. Participants were selected using purposive sampling based on their involvement in digital health initiatives. Data were analyzed using thematic analysis supported by NVivo software, with triangulation applied to enhance the credibility of findings. Results: The study identified four major themes influencing digital transformation in public health services: digital infrastructure readiness, collaborative innovation among stakeholders, institutional and governance challenges, and perceived impacts on service delivery. Participants emphasized that integrated health information systems improved reporting efficiency and program monitoring. However, challenges related to system interoperability, regulatory fragmentation, and institutional coordination were reported as barriers to effective implementation. Conclusion: Digital transformation in public health services is shaped by the interaction between technological infrastructure, collaborative innovation, and governance capacity. Strengthening digital health governance, promoting cross-sector collaboration, and improving institutional digital capacity are essential to ensure sustainable and effective digital health implementation.